An excess of goodness? Volunteering among aid professionals in Cambodia. (September 2017) - Fechter, Anne-Meike
This article explores the meaning of volunteering among professional aid workers. While they experience disenchantment in their daytime work, volunteering provides them with benefits lacking in their paid jobs. At the same time, a compensatory model does not capture the complex dimensions of this relationship. One motive behind their professional work – bringing about positive change for others – is also the driving force behind their voluntary practices. Such excess of doing good may be indicative of their overall commitment. If aid workers make sense of their actions within a framework of alienated labour, rendering their waged aid work as a commodity, volunteering emerges as a remedial response. At the same time, their paid and unpaid work is animated by the impulse of giving. Such co-existence implies that gifts and commodities are not mutually exclusive; or indeed that both can be understood, following Parry (1986), as emerging from a highly developed capitalist system.